Penjatuhan Pidana dalam Tindak Pidana Pelanggaran Hak Desain Industri Mengacu pada Putusan Kasasi MA No 1609 K/Pid.Sus/2020 - Citra Annisya Juwansari; Mery Ajeng Wijayanti; Karyn Firda Faridyan; Siti Nur Halimah Monica (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Industrial design is a creation about the shape, configuration, or composition of lines or colors, or lines and colors or a combination thereof in three-dimensional or two-dimensional forms that give an aesthetic impression. Diansari Puri Plastindo who has a Bath Tub Industrial Design certificate registered with the Directorate of Copyright and Industrial Design at the Indonesian Ministry of Law and Human Rights with Registration Number IDD00000035015. There is a problem formulation, namely Does the Judge's Consideration state that the article indicted by the Public Prosecutor based on Article 54 paragraph juncto Article 9 paragraph Law Number 31 of 2000 concerning Industrial Design in conjunction with Article 55 paragraph 1 of the Criminal Code is in accordance with the defendant's actions?, and What are the Judges' Considerations in imposing the Criminal Law in Decision Number 1609 K/Pid. Sus/2020 is in accordance with the Criminal System in Indonesia? Conclusions: First, the judge's consideration stated that the article indicted by the public prosecutor based on Article 54 paragraph Juncto Article 9 paragraph Law Number 31 of 2000 concerning Industrial Design in conjunction with Article 55 paragraph 1 of the Criminal Code is in accordance with the actions of the defendant. The two judges' considerations in imposing a sentence in Decision.